Offline and Online Sexual Risk Behavior among Youth in the Netherlands: Findings from “Sex under the Age of 25” - De Graaf, Hanneke; Verbeek, Mirthe; Van den Borne, Marieke; Meijer, Suzanne (Frontiers in Public Health, 2018)
Sexually developing adolescents and emerging adults face sexual health risks as well as potentially negative outcomes of online sexual behaviors. The goal of this study was to describe three categories of sexual risk behavior: (1) behavior related to STI/HIV, (2) behavior related to unplanned pregnancy, and (3) online sexual risk behavior. In addition, we investigated whether these behaviors are actually related to negative (health) outcomes. For this purpose, we used data from a Dutch probability survey: “Sex under the age of 25.” Adolescents and emerging adults aged 12 through 24 (8,053 boys and 12,447 girls) completed a digital questionnaire, including measures of the risk of STI/HIV and pregnancy, online sexual behavior and non-consensual sex. Chi-square tests and logistic regressions were used to test for gender and age differences and compute associations between risk behavior and negative outcomes. The results showed that the risk of unplanned pregnancy is low in the Netherlands. It seems that adolescents and emerging adults are less aware of the risk of STI/HIV than of the risk of pregnancy. About 11% of the participants had had more than one partner in the last 6 months and had not used condoms consistently with their last partner, and these participants had a 3.56 times higher likelihood of ever being diagnosed with an STI. Although many young people stop using condoms with their partner after a while, most of them did not get tested for STIs. More emerging adults (aged 18–24) engage in sexting (sending personal nude pictures and sex videos to others), but the chance that these images are shared with other people than the intended recipient is higher among adolescents (aged 12–17). The results of this study can guide professionals working in sex education and sexual health services to focus their efforts on the risk behaviors in the Netherlands that deserve most attention.